Distortional hardening concept for modeling anisotropic/asymmetric plastic behavior of AZ31B magnesium alloy sheets. (July 2017) - Lee, J.; Kim, S.-J.; Lee, Y.-S.; Lee, J.-Y.; Kim, D.; Lee, M.-G.
Abstract: A continuum-based approach for describing the plastic hardening behavior of magnesium alloy sheets subjected to non-proportional strain path changes at room temperature is presented. The constitutive model is based on an anisotropic distortional yield function that combines a stable component and a fluctuating component. The stable component initiates the yield criterion that characterizes the typical strength differential (SD) effect between tension and compression in magnesium alloys at room temperature. The evolution of the fluctuating component is reformulated based on its cubic metal counterpart to represent the deformation behavior of magnesium alloys, which consists of slip- and twinning-dominant deformation modes. To validate the proposed model, a predictor–corrector numerical algorithm was implemented in a finite element (FE) program by using a user material subroutine, and its numerical accuracy was evaluated by iso-error map analysis. Comparison of the experimental and simulated results obtained for various loading path changes showed that, although the model was not formulated using the kinematic hardening concept, the model could reproduce complex features of the stress–strain responses of an AZ31B magnesium alloy sheet under non-proportional loading paths, i.e., asymmetric hardening behavior under tension and compression, the sigmoidal nature of the hardening curve during monotonic compression and compression followed by tension. Highlights: Enhanced distortional hardening law for Mg alloys was proposed. The predictor-corrector stress integration algorithm was implemented and evaluated by the iso-error maps. Experimental results under strain path changes were accurately predicted using the HAH-HCP model.